Triggered Drug Release From Liposomes: Exploiting the Outer and Inner Tumor Environment - Franco, Marina Santiago; Gomes, Eliza Rocha; Roque, Marjorie Coimbra; Oliveira, Mônica Cristina (Frontiers in Oncology, 2021)
Since more than 40 years liposomes have being extensively studied for their potential as carriers of anticancer drugs. The basic principle behind their use for cancer treatment consists on the idea that they can take advantage of the leaky vasculature and poor lymphatic drainage present at the tumor tissue, passively accumulating in this region. Aiming to further improve their efficacy, different strategies have been employed such as PEGlation, which enables longer circulation times, or the attachment of ligands to liposomal surface for active targeting of cancer cells. A great challenge for drug delivery to cancer treatment now, is the possibility to trigger release from nanosystems at the tumor site, providing efficacious levels of drug in the tumor. Different strategies have been proposed to exploit the outer and inner tumor environment for triggering drug release from liposomes and are the focus of this review.